Development of Traffic Infrastructure in the Croatian Traffic System - Šimulčik, Damir; Bošnjak, Ivan; Ban, Ivo (Promet - Traffic&Transportation, 2012)
Valorisation of tourist potentials as a guideline for theachievement of strategic determinants of Croatia ’s tourism isone of the main determinants of the economic system ofCroatia for the period of upcoming years. Realisation of this determinantis not possible without the implementation of a longterm transport policy and a policy for financing the constructionand maintenance of traffic infrastructure facilities, alongwith other already mentioned factors which exist within theframework of social and economic reality including tourist indusl!y.This indicates that Croatia must take a clear stand with respectto the determining of the traffic infrastructure constructionand maintenance strategy, as the main precondition realisingthe strategic determinants ofCroatian tourism.The authors stmt from the basic conditions of determiningthe strategy traffic infrastructure facilities construction andmaintenance in the function of attaining already set developmentstrategies ofCroatia’s tourism. Synchronisation as a pa1tof the process of realisation is possible if it is possible to determinethe feasibility and capability of those responsible for therealisation of the strategy and development of traffic infrastructureand tourist indus!ly. If it is not realised on the level of itsfeasibility, then the only thing we get is one more declarativedocument in the field of economic activity.